Improved properties of keratin-based bioplastic film blended with microcrystalline cellulose : a comparative analysis - Alashwal, Basma Yahya; Saad Bala, M.; Gupta, Arun; Sharma, Swati; Mishra, Puranjan (Elsevier Ltd, 2019)
In the present study, bioplastic films were developed using the different ratio of keratin extracted from chicken feathers and cellulose. Firstly, bioplastic (K-60) was developed from the keratin, extracted from the chicken feathers using an alkaline agent (NaOH), and mixed with PVA/glycerol to synthesize protein-based bioplastic. Further, microcrystalline cellulose (2%) was used as an additive to K-60 bioplastic to develop an improved bioplastic (KC-60). The results of functional group analysis using FT-IR, showed the conformational arrangements of the keratin protein have mostly amides I–III and O–H groups in the bioplastic reinforced with microcrystalline cellulose and showed the substantial hydrogen bonding. The scanning electron microscopy analysis suggested the appropriate morphologies without edge, holes and cavities. The X-Ray diffraction analysis suggested the strong crystalline characteristics of synthesized bioplastic. Finally, the thermogravimetric analysis of K-60 and KC-60, showed the greater cross-linking efficiency between cellulose and keratin at higher temperature. Therefore, the results presented the development of keratin-based bioplastics with high structural strength and morphology good crystallinity which can be used in biomedical applications and manufacturing of food containers and others.